2020
DOI: 10.3390/app11010253
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Relaxation of DRWDs in OSDs under Constant/Variable Amplitude Cyclic Loading

Abstract: An orthotropic steel deck (OSD) has a complicated structure, and its fatigue life is mainly determined by various welding details. Fatigue assessment of deck-to-rib welding details (DRWDs) under long-term train loads is an important concern for engineers. Properly assessing the initial residual stress and the mechanism of stress relaxation in DRWDs under long-term external loading is a prerequisite for predicting the fatigue damage and service life of OSDs. In this paper, a finite element analysis method is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…This is because the stress magnitude at the crack front exceeds the yield strength as the load amplitude increases and the residual stresses are relaxed after the unloading. These results are in good agreement with the results obtained in [24] and [25].…”
Section: Effect Of Load Amplitudesupporting
confidence: 92%
See 2 more Smart Citations
“…This is because the stress magnitude at the crack front exceeds the yield strength as the load amplitude increases and the residual stresses are relaxed after the unloading. These results are in good agreement with the results obtained in [24] and [25].…”
Section: Effect Of Load Amplitudesupporting
confidence: 92%
“…The result presented in Figure 9 is in agreement with [39]. Zhong et al [24] observed the similar results.…”
Section: Effect Of Stress Ratio (R)supporting
confidence: 89%
See 1 more Smart Citation
“…The amounts of relaxation are almost up to 30% or more, except the measuring point at the outside weld on the U-rib. It is noted that the amount of WRS relaxation does not increase with the stress amplitude increases as expected [12][13] [14], although it also depends on the initial WRS at the same time [15]. Principally, the reasons behind this phenomenon are that the test data are limited, and the microstructure of each test specimen after welding is discrepant.…”
Section: Effect Of the Load Amplitude On The Wrs Relaxationmentioning
confidence: 96%
“…Of the limited WRS measurement on OSDs reported in the literatures, only a few have been conducted in an innovative double-side welded RTD joints, especially for the magnitude and distribution of transverse WRS. Moreover, WRS of RTD joints will release under cyclic loading [12][13] [14]. WRS relaxation may occur when dislocation movements engender induced by additional applied loads or thermal energy, which change the local plastic constraints and results in residual stress redistribution [15] [16].…”
Section: Introductionmentioning
confidence: 99%